Study of the interaction between sodium salts of (2E)‐3‐(4'‐halophenyl)prop‐2‐enoyl sulfachloropyrazine and bovine serum albumin by fluorescence spectroscopy. (12th April 2012) - Luo, Xuan; Du, Chuanrong; Wei, Jinrui; Deng, Jiang; Lin, Yijie; Lin, Cuiwu
ABSTRACT: Three sodium salts of (2 E )‐3‐(4'‐halophenyl)prop‐2‐enoyl sulfachloropyrazine (CCSCP) were synthesized and their structures were determined by 1 H and 13 C NMR, LC‐MS and IR. The binding properties between CCSCPs and bovine serum albumin (BSA) were studied using fluorescence spectroscopy in combination with UV–vis absorbance spectroscopy. The results indicate that the fluorescence quenching mechanisms between BSA and CCSCPs were static quenching at low concentrations of CCSCPs or combined quenching (static and dynamic) at higher CCSCP concentrations of 298, 303 and 308 K. The binding constants, binding sites and corresponding thermodynamic parameters (Δ H, Δ S, Δ G ) were calculated at different temperatures. All Δ G values were negative, which revealed that the binding processes were spontaneous. Although all CCSCPs had negative Δ H and positive Δ S, the contributions of Δ H and Δ S to Δ G values were different. When the 4'‐substituent was fluorine or chlorine, van der Waals interactions and hydrogen bonds were the main interaction forces. However, when the halogen was bromine, ionic interaction and proton transfer controlled the overall energetics. The binding distances between CCSCPs and BSA were determined using the Förster non‐radiation energy transfer theory and the effects of CCSCPs on the conformation of BSA were analyzed by synchronous fluorescence spectroscopy. Copyright © 2012 John Wiley & Sons, Ltd.